Endoplasmic reticulum stress pathway mediates T-2 toxin-induced chondrocyte apoptosis. (December 2021) - Liu, Yi-Nan; Mu, Yu-Dong; Wang, Hui; Zhang, Meng; Shi, Ya-Wen; Mi, Ge; Peng, Lei-Xuan; Chen, Jing-Hong
Abstract: T-2 toxin leads to chondrocyte apoptosis and excessive extracellular matrix degradation. The aim of this study is to investigate if endoplasmic reticulum stress (ERS) – initiated apoptosis is involved in the chondrocyte damage induced by T-2 toxin. In vivo, rats were divided into a control group, T-2 toxin 200 ng/g BW/d group, the protein levels of GRP78, CHOP, and caspase-12 were detected using immunohistochemistry in articular cartilage tissues. In vitro, C28/I2 and ATDC5 chondrocytes were treated with various concentrations of T-2 toxin. For the salubrinal protection assay, cells were pretreated with 20 μM salubrinal for 1 h, and treated with and without T-2 toxin for 24 h. The cell viability was determined using the MTT assay; and the cell apoptosis was determined using the Flow Cytometry Assay; the mRNA and protein levels of the ERS markers and ECM were determined using RT-PCR and western blotting. This study found that the expressions of GRP78, CHOP, and caspase-12 is higher in T-2 toxin group than in control group both in vivo and in vitro, and the T-2 toxin administration promoted chondrocyte apoptosis, suppressed matrix synthesis, and accelerated cellular catabolism via the ERS signaling pathway. In addition, this study found that salubrinal prevented chondrocyte injury by inhibiting ERS-mediated apoptosis via the PERK-eIF2α-ATF4-CHOP signaling pathway. Collectively, this study provides a new clue to elucidate the mechanism of T-2 toxin-induced chondrocyte damage, and presents a novel therapeutic possibility of salubrinal for Osteoarthropathy such as osteoarthritis (OA) and Kaschin-Beck disease (KBD).